(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This scientific study provides information on the origin, history, role, epidemiology, and causes of infectious diseases. The incidence of infectious diseases in the population is of particular importance. A lot of information has been accumulated on the study of various aspects of infectious diseases. Today, scientists are working diligently on unresolved problems in this area. Despite the progress made in eliminating or reducing many infectious diseases, these diseases still cause great harm to the health of the population. One of the main tasks of the Ministry of Health of the Republic of Uzbekistan today is to combat infectious diseases and prevent them. Infectious diseases have their own laws, which are the occurrence of epidemics after a certain period of time or the emergence of new infectious diseases on the eve of the elimination of some diseases.